Metformin hydrochloride ameliorates adiponectin levels and insulin sensitivity in adolescents with metabolic syndrome - Liang, Li (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2006)
OBJECTIVES: Metabolic syndrome (MS) in adolescents was reported to be closely associated with cardiovascular diseases in adulthood. However, no unified treatment measure for MS in adolescents is currently available. The aim of this study was to measure the changes of serum adiponectin levels, insulin sensitivity and other biochemical markers after metformin therapy in adolescents with MS, which might provide some information for set up a unified therapeutic measure for MS in adolescents